Efektivitas Pembelajaran STEAM Berbasis PJBL Dalam Meningkatkan Kreativitas Mahasiswa Teknik Sipil Mata Kuliah Mekanika Fluida Dan Hidrolika - Ferawati Artauli Hasibuan; Tetti Hasibuan (Concept: Journal of Social Humanities and Education, 2023)
The development of increasingly sophisticated technology requires every individual to be able to understand and apply this technology in everyday life. For this reason, higher creativity is needed in order to be able to think creatively in discovering new things, be it new methods or works and especially being able to solve the problems at hand. Thus, in lectures every student is required to be able to understand lecture material well so that it can be practiced in his life later. One of the methods used to solve this problem, in this study, will be learning using the STEAM method through Project Based Learning (PjBL) for students in semester II (two) of the civil engineering study program. PjBL-based STEAM learning is expected to foster student creativity, especially in creating new works through a project being worked on. The purpose of this study was to find out how effective the use of the PjBL-based STEAM learning method was at the student level, and to find out how student creativity was after the action, whether it increased or not. The research method used is the class action method. Based on the results of the study, it was concluded that the application of the PjBL-based STEAM learning method was feasible for use in the learning process and it was suggested that it could be implemented for further learning. Student creativity has increased through the application of STEAM. This can be seen from the increase in the percentage of student skills for each component observed, namely 12.38% from cycle I in the fairly good category to cycle II in the good category.